EFL Students’ Academic Writing Challenges and Teachers’ Feedback Strategies in Upper Secondary School - Setyawati, Vivin (Mastery: Master of English Language Journal, 2025)
This study investigates EFL students’ academic writing challenges and teachers’ feedback strategies in upper secondary school. Employing a qualitative research design, data were collected through semi-structured interviews, classroom observations, and document analysis involving EFL students and English lecturers at a university. The findings reveal that students experience major difficulties in grammatical accuracy, academic vocabulary, idea organization, and coherence, influenced by differences in rhetorical conventions between their first language and English. The results also indicate that teachers predominantly use written corrective feedback, often combined with oral explanations, to address these challenges. However, the effectiveness of feedback depends largely on its clarity and specificity, as some students struggle to interpret general or unclear comments. This study concludes that more targeted and learner-centered feedback strategies are essential to enhance EFL students’ academic writing development in upper secondary school.